2010
DOI: 10.1007/s00431-010-1349-6
|View full text |Cite
|
Sign up to set email alerts
|

Destructive pulmonary staphylococcal infection in a boy with hyper-IgE syndrome: a novel mutation in the signal transducer and activator of transcription 3 (STAT3) gene (p.Y657S)

Abstract: The mutation,p.Y657S,in SH2 domain of STAT3 is a disease-causing mutation in the boy with HIES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…In HIES patients of Chinese descent, four with de novo heterozygous STAT3 mutations -two with R382W and Q469R in Taiwan and another two with H437P and Y657S in mainland China (Liu et al 2010;Xie et al 2010) -and the first homozygous DOCK8 deletion in one siblings were identified. Four patients with higher severity scores of the AD-HIES phenotype and three with the AR-HIES phenotype have the wild type STAT3, TYK2 and DOCK8.…”
Section: Discussionmentioning
confidence: 98%
“…In HIES patients of Chinese descent, four with de novo heterozygous STAT3 mutations -two with R382W and Q469R in Taiwan and another two with H437P and Y657S in mainland China (Liu et al 2010;Xie et al 2010) -and the first homozygous DOCK8 deletion in one siblings were identified. Four patients with higher severity scores of the AD-HIES phenotype and three with the AR-HIES phenotype have the wild type STAT3, TYK2 and DOCK8.…”
Section: Discussionmentioning
confidence: 98%
“…Underlined mutations were identified in patients from the current study; mutations not underlined were identified in previous studies. [2–4,28,29,33,35,36,41,47,52,55,60-62,70,71] The positions of all known mutations are indicated in amino acid nomenclature, with the exception of mutations starting with c. at the bottom, which are shown in nucleotide nomenclature.…”
Section: Figurementioning
confidence: 99%
“…Since 2007, up to 230 STAT3-deficient patients have been reported in individual case reports [2–4,13, 33, 35, 41, 43, 44, 55, 61, 68, 71] or national or international series, including 8 patients (Japan), [47] 37 (United States and Europe), [60] 12 (Lebanon and Europe), [29] 50 (international), [28] 64 (international), [70] and 48 patients (international). [62] However, most reports have focused on the molecular and cellular defects of the patients, providing little clinical information.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, signal transducer and activator of transcription 3 (STAT3) mutations were found to be the cause of the sporadic and autosomal dominant hyper‐IgE syndrome (AD‐HIES) , and patients showed extremely low or absent T helper 17 cells (Th17) in their peripheral blood . Few Chinese cases of HIES due to STAT3 mutations were reported in Hong Kong, Taiwan and mainland China ; no investigations have analysed Th17 cell numbers in patients with HIES in mainland China. In this study, we described the phenotypes of Chinese children with HIES, carried out STAT3 gene sequencing in all nine patients and quantified Th17 cell numbers in seven patients.…”
Section: Introductionmentioning
confidence: 99%